Geographic variation in human papillomavirus–related oropharyngeal cancer: Data from 4 multinational randomized trials. (8th January 2016) - Mehanna, Hisham; Franklin, Natalie; Compton, Natalie; Robinson, Max; Powell, Ned; Biswas–Baldwin, Nigel; Paleri, Vindh; Hartley, Andrew; Fresco, Lydia; Al‐Booz, Hoda; Junor, Elizabeth; El‐Hariry, Iman; et al.
Abstract: Background: There are variations in the proportions of head and neck cancers caused by the human papillomavirus (HPV) between countries and regions. It is unclear if these are true variations or due to different study designs and assays. Methods: We tested formalin‐fixed paraffin‐embedded diagnostic biopsies for p16 immunohistochemistry and HPV‐DNA (by polymerase chain reaction [PCR] and in situ hybridization [ISH]) using validated protocols on samples from 801 patients with head and neck cancer recruited prospectively between 2006 and 2011 in 4 randomized controlled trials (RCTs). Results: Twenty‐one percent of patients (170 of 801) showed both HPV‐DNA and p16‐positivity, detected almost exclusively in oropharyngeal cancer (55%; 15 of 302); and only 1% of the patients (5 of 499) with nonoropharyngeal cancer were HPV positive. HPV‐positive oropharyngeal cancer differed between Western and Eastern Europe (37%, 155 of 422 vs 6%, 8 of 144; p < .0001) and between Western Europe and Asia (37% vs 2%; 4 of 217; p < .0001). Other independent determinants of HPV positivity were tumor site and smoking. Conclusion: This is the first study to establish geographic variability as an independent risk factor in HPV‐positive oropharyngeal cancer prevalence, with higher prevalence in Western Europe. © 2016 The Authors Head & Neck Published by Wiley Periodicals, Inc. Head Neck 38 : E1863–E1869, 2016